Enhancing Al2O3 composites: In situ synthesis and nanostructure transformation of ZIFs for mechanical and conductivity control - Bayrak, Kuebra Guercan; Duden, Enes Ibrahim; Cakan, Niyaz; Caglar, Mujdat; Erkartal, Mustafa; Sen, Unal; Erkartal, Mustafa (Springer Heidelberg, 2025)
Integrating nanocarbon materials into ceramic matrices offers potential improvements in mechanical, electrical, and thermal properties. In this study, in situ synthesis and transformation of zeolitic imidazolate framework (ZIF8) into nanocarbon phases within an Al2O3 matrix were achieved using spark plasma sintering at 1500 degrees C and 50 MPa. A uniform dispersion of ZIF8-derived nanocarbons led to significant grain refinement and the formation of a conductive network. Increasing ZIF8 content reduced hardness (from 18.71 to 8.04 GPa) and fracture toughness (from 5.19 to 3.90 MPam1/2) due to higher porosity and softer carbon phases. However, electrical conductivity improved substantially, reaching 2500 S/m with 15 wt% ZIF8. Conversely, thermal conductivity decreased due to intensified phonon scattering and the finer-grained structure. These results demonstrate the dual functionality of ZIF8-derived nanocarbon in Al2O3 composites, balancing enhanced electrical performance with thermal management for advanced applications in electronics and energy systems.
Keywords: Ceramics; Metal-Organic Framework (Mof); Powder Processing; Sintering; Hardness; Electrical Properties